When and how to repower energy systems? A four strategies-based decision model. (June 2022) - Safaei, Fatemeh; Tazi, Nacef; Châtelet, Eric; Bouzidi, Youcef
Abstract: Repowering systems is a long-lasting managerial endeavor where decision-makers face maintenance and optimization problems. The decision time to repower an energy system is one of the most important matters in this field. Also, in the real-world, each component of the system has different versions available in the market, so choosing the best version of components can be one of the valuable and practical issues in repowering a system. Therefore, decision-makers need optimal repowering policies in order to generate the optimal combination of system's components as well as the optimal time to repower this system with respect to important concerns such as cost, availability and safety issues. This paper provides a first-step decision-making model based on four independent repowering strategies for energy systems. A case study from offshore wind turbine system is presented afterwards to demonstrate the effectiveness of the presented policies. This decision support tool deals with the optimal repowering time and the best combination of components based on cost, availability, and safety constraints.